Efektivitas Pembelajaran Terbaru Melalui Spada Untirta Sebagai Metode Kajian Difusi Inovasi - Rabeka Herdiani; Yayan Saryani; Hanifa Fajriani; Rangga Galura Gumelar (Jurnal Ilmiah Wahana Pendidikan, 2023)
Demanded by the development of the times, which makes education staff and students inevitably, ready or not ready, must face advances in information technology that occur in educational institutions. SPADA Untirta is an Online Learning System developed by Sultan Ageng Tirtayasa University. This study uses the theory of Diffusion of Innovation to determine the effectiveness of the online learning system used by Untirta. Using a quantitative method with a population of Untirta master of communication students batch 2021. The results show that each stage of innovation diffusion in the use of SPADA UNTIRTA for online learning media has been exceeded even though there are still some obstacles. These obstacles include external obstacles but are still considered effective because 39.4% of students stated that they were quite satisfied in using SPADA UNTIRTA